2023
DOI: 10.1021/acsanm.2c05061
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Lasing Using Individual GaN Nanobelts

Abstract: It is crucial to realize gallium nitride (GaN) ultraviolet nanolasing to cater the needs of on-chip integration and optical interconnection, quantum information processing, and high-density storage. The key challenge is preparing freestanding high-crystal quality GaN micro/nanostructures with a controllable structure to realize single-mode ultraviolet nanolasing with a low threshold. Here, a freestanding GaN nanobelt is prepared using the graphically epitaxial lift-off technique, and multimode ultraviolet Fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…40 Recently, many groups have focussed on the design and fabrication of three-dimensional porous ceramics, polymers and composite-based piezoelectric devices. 12,23,[41][42][43][44][45][46] Porous piezoelectric materials were reported to show high output sensitivity and a higher piezoelectric harvesting gure of merit over dense materials. 47 Previous studies demonstrated that porous materials featuring a lower modulus have improved compression deformation and also the emergence of local stress hot spots improved the output performance.…”
Section: Introductionmentioning
confidence: 99%
“…40 Recently, many groups have focussed on the design and fabrication of three-dimensional porous ceramics, polymers and composite-based piezoelectric devices. 12,23,[41][42][43][44][45][46] Porous piezoelectric materials were reported to show high output sensitivity and a higher piezoelectric harvesting gure of merit over dense materials. 47 Previous studies demonstrated that porous materials featuring a lower modulus have improved compression deformation and also the emergence of local stress hot spots improved the output performance.…”
Section: Introductionmentioning
confidence: 99%